USE OF INTERNATIONAL MARKETING STRATEGIES IN THE SUSTAINABLE DEVELOPMENT OF THE SERVICE FIELD (Marketing Journal, 2026)
This scientific article provides an in -depth analysis of the theoretical, methodological, and practical aspects of applying international marketing strategies in ensuring the sustainable development of the service sector. The study reveals the growing role of the service sector in the global economy and examines the mechanisms for integrating the concept of sustainable development with marketing strategies. The № 1 -SON YANVA R, 202 6-YIL 454 research employs systematic analysis, a comparative approach, empirical observation, analysis of secondary statistical data, and strategic marketing models. The findings demonstrate that the implementation of digital, differentiated, and environmentally oriented international marketing strategies in the service sector plays a significant role in ensuring sustainable economic growth, enhancing competitiveness, and increasing consumer satisfaction.
Keywords: service sector; sustainable development; international marketing strategies; services marketing; global market; digital marketing; green marketing